High temperature sintering: Microstructure, density, dimensional and geometrical precision - Cristofolini, Ilaria; Molinari, Alberto; Tesfaye, Samuel; Federici, Matteo; Weber, H.; De Nicolò, Alessandro (Advances in Powder Metallurgy and Particulate Materials - 2014, Proceedings of the 2014 World Congress on Powder Metallurgy and Particulate Materials, PM 2014, 2014)
The effect of high temperature on dimensional change, porosity, microstructure, dimensional and geometrical characteristics of parts is analyzed. On increasing the sintering temperature shrinkage increases and anisotropy of dimensional change gets progressively attenuated. The fraction of the load bearing section increases and the microstructure of the ferrous matrix may result unmodified, hardened (enhanced diffusion of alloying elements), softened (decarburizing). Sintering temperature may be increased up to 1350°C without affecting dimensional and geometrical precision of steel parts.
CRIS-Team Scopus Importer:2023-03-17